Naïve T Cells in Immunosuppression Diseases: Human Immunodeficiency Virus and Cytomegalovirus - Kent Wijaya Setiawan; Ferry Sandra (Cell and BioPharmaceutical Institute, 2018)
Dynamic changes of naïve T cells determine mature T cells activity in cell-mediated immune response. It is important to understand the mechanism of homeostasis maintenance affect response to novel antigen toward T cell receptor-major histocompatibility complex interaction. Most of the analysis of naïve T cells relies on flow cytometric immunophenotyping to observe surface antigen alteration within maturation stage. The combination of different surface molecules, such as the cluster of differentiation 62L (CD62L), C-C chemokine receptor type 7 (CCR7), CD27, CD28, and CD45, can give satisfied discrimination between naïve T cells and other subsets. This parameter can be used to monitor the dynamic change of naïve T cells in some chronic diseases, like human immunodeficiency virus (HIV) and cytomegalovirus (CMV). Most of the patient experience loss of naive T cells due to a chronic immune response, which related to apoptotic induction in proliferating cells by viral activity. Some pathogens trigger the migration of naive T cells into lymph nodes to facilitate direct contact with the host cells. The virus infects the cells, use cells proliferation to multiply, and induce apoptosis of host cells after the virions released. Alteration of naive T cells in chronic disease becomes a parameter to oversee the treatment and to determine the future prognosis of the disease. In highly active antiretroviral therapy for HIV infection, observation of naïve T cells and combination of surface molecules, CD45RO− and CD27+ is used to show the improvement and proliferation rate of total naïve T cells. On the other hand, the transformation of naïve T cells into CMV-specific T cells become really important in CMV prognosis. These conditions suggest that dynamic change of naïve T cells affect to the clinical condition of chronic disease patients.Keywords: naïve T cells, immunophenotyping, HIV, CMV